Primary effusion lymphoma enhancer connectome links super-enhancers to dependency factors - Wang, Chong; Zhang, Luyao; Ke, Liangru; Ding, Weiyue; Jiang, Sizun; Li, Difei; Narita, Yohei; Hou, Isabella; Liang, Jun; Li, Shijun; Xiao, Haipeng; Gottwein, Eva; et al. (Nature communications, 2020)
Primary effusion lymphoma (PEL) has a very poor prognosis. To evaluate the contributions of enhancers/promoters interactions to PEL cell growth and survival, here we produce H3K27ac HiChIP datasets in PEL cells. This allows us to generate the PEL enhancer connectome, which links enhancers and promoters in PEL genome-wide. We identify more than 8000 genomic interactions in each PEL cell line. By incorporating HiChIP data with H3K27ac ChIP-seq data, we identify interactions between enhancers/enhancers, enhancers/promoters, and promoters/promoters. HiChIP further links PEL super-enhancers to PEL dependency factors MYC, IRF4, MCL1, CCND2, MDM2, and CFLAR. CRISPR knock out of MEF2C and IRF4 significantly reduces MYC and IRF4 super-enhancer H3K27ac signal. Knock out also reduces MYC and IRF4 expression. CRISPRi perturbation of these super-enhancers by tethering transcription repressors to enhancers significantly reduces target gene expression and reduces PEL cell growth. These data provide insights into PEL molecular pathogenesis. Primary effusion lymphoma (PEL) has a very poor prognosis. Here, the authors perform H3K27ac HiChIP in PEL cells and generate the PEL enhancer connectome, linking enhancers and promoters in PEL, as well as super-enhancers to dependency factors.